2012
DOI: 10.1167/iovs.12-10275
|View full text |Cite
|
Sign up to set email alerts
|

Macular Pigment Imaging in AREDS2 Participants: An Ancillary Study of AREDS2 Subjects Enrolled at the Moran Eye Center

Abstract: PURPOSE. Age-Related Eye Disease Study 2 (AREDS2) is a randomized, placebo-controlled study designed to determine whether supplementation with 10 mg of lutein and 2 mg of zeaxanthin per day can slow the rate of progression of agerelated macular degeneration (AMD). Although some biomarkers of response to carotenoid supplementation such as serum concentrations are part of the AREDS2 protocol, measurement of carotenoid concentrations in the eye and other tissues is not. In this approved ancillary study, macular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
5
32
3
Order By: Relevance
“…For example, a baseline study from Utah observed that its subjects had surprisingly high MPOD levels at the baseline visit of the study, probably because of an inadequate 30-d supplementfree washout period. This finding was consistent with the observation that 70% of Utah subjects had been taking lutein and zeaxanthin supplements regularly for many years before enrollment (142). Follow-up MPOD measurements of these subjects recorded at scheduled visits every 6 mo during the study period did not provide any convincing evidence of an effect of supplementation.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, a baseline study from Utah observed that its subjects had surprisingly high MPOD levels at the baseline visit of the study, probably because of an inadequate 30-d supplementfree washout period. This finding was consistent with the observation that 70% of Utah subjects had been taking lutein and zeaxanthin supplements regularly for many years before enrollment (142). Follow-up MPOD measurements of these subjects recorded at scheduled visits every 6 mo during the study period did not provide any convincing evidence of an effect of supplementation.…”
Section: Introductionsupporting
confidence: 86%
“…No macular pigment optical density (MPOD) measurements were included in the AREDS2 protocol, because the image-based instrumentation had not been sufficiently standardized at that time. Moreover, the psychophysical methods were thought to require too much time and subject training during the very busy study visits, but an ancillary study conducted at the Utah site had the equipment and experience to measure macular pigment with dual-wavelength autofluorescence imaging (142).…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is different from about five distinguishable MP distribution patterns observable in healthy adults 13,15 and AMD patients. 23 In all nine prematurely born infants, MP was found to be absent. In all these cases, a distinguished macular region could not be detected, as seen from a representative B-chip image in Fig.…”
Section: Mp Reflection Image Features and Clinical Resultsmentioning
confidence: 88%
“…The behavior is similar to the respective correlation in adult eyes. 13,15,23 While at any particular age, the peak MPOD levels can differ by about one order of magnitude between subjects, there is on average a steady linear increase of MPOD levels over the first 6 years of life, as shown in Fig. 11.…”
Section: Mp Reflection Image Features and Clinical Resultsmentioning
confidence: 95%
“…Four discrete MP distributions have been described by Trieschman et al [5] while Bernstein et al [6] categorized five distinct MP distribution subgroups.…”
Section: Introductionmentioning
confidence: 99%